ON AUTOMORPHISMS OF THE RELATIVELY FREE GROUPS SATISFYING THE IDENTITY $[x^n; y] = 1$ - Stepanyan, Sh.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
We prove that if an automorphism j of the relatively free group of the group variety, defined by the identity relation $[x^n; y] = 1$, acts identically on its center, then j has either infinite or odd order, where $n≥ 665$ is an arbitrary odd number.
Keywords: relatively free group, automorphism, periodic group